Przestępstwo kradzieży w prawie oraz praktyce karnej Rosji i Polski - Solodov, Denis (Studia Prawnoustrojowe, 2019)
Theft belong to the group of statistically most commonly committed crimes in both Poland and Russia. The author compares the criminal law regulations in both countries, shows a differentiated approach of the legislature, exposes the basic problems of the legal practice.